Influence of preoperative oral rehydration on arterial plasma rocuronium concentrations and neuromuscular blocking effects: A randomised controlled trial. Issue 1 (January 2017) - Ishigaki, Sayaka; Ogura, Takahiro; Kanaya, Ayana; Miyake, Yu; Masui, Kenichi; Kazama, Tomiei
Abstract : BACKGROUND: The influence of preoperative rehydration on the action of rocuronium has not yet been investigated. OBJECTIVE: The objective is to evaluate the hypothesis that preoperative rehydration lowers arterial rocuronium plasma concentrations and changes its associated neuromuscular blocking effects during induction of anaesthesia. DESIGN: Randomised, single-blinded study. SETTING: A secondary hospital from October 2013 to July 2014. PATIENTS: In total, 46 men undergoing elective surgery were eligible to participate and were randomly allocated into two groups. Exclusion criteria were severe hepatic, renal or cardiovascular disorder; neuromuscular disease; history of allergy to rocuronium; BMI more than 30 kg m −2 ; receiving medication known to influence neuromuscular function. INTERVENTION: Participants received 1500 ml of oral rehydration solution (rehydration group) or none (control group) until 2 hours before anaesthesia. Arterial blood samples were obtained 60, 90 and 120 s and 30 min after rocuronium (0.6 mg kg −1 ) administration during total intravenous anaesthesia. Responses to 0.1-Hz twitch stimuli were measured at the adductor pollicis muscle using acceleromyography. MAIN OUTCOME MEASURES: Arterial plasma rocuronium concentrations. RESULTS: Arterial plasma rocuronium concentrations at 60, 90 and 120 s in the rehydration and control groups were 9.9 and 13.7, 6.8 and 9.5 and 6.2 and 8.1 μg ml −1, respectively ( P  = 0.02, 0.003 and 0.02, respectively); the onset times in the rehydration and control groups were 92.0 and 69.5 s ( P  = 0.01), and the times to twitch re-appearance were 25.3 and 30.4 min ( P  = 0.004), respectively. CONCLUSION: Preoperative rehydration significantly reduces arterial plasma rocuronium concentrations in the first 2 minutes after administration, prolonging the onset time and shortening the duration of effect. A higher dose or earlier administration should be considered for patients who receive preoperative rehydration. TRIAL REGISTRATION: Umin identifier: UMIN000011981.